The bureaucratic elite in Nigeria - Nwankwo, Godson Onyekwere (1980)
Nigeria has been under, within the past 70 years or more, a colonial regime until 1960, a civilian democratic regime until 1966, and four military regimes until 1979. It is presently under a presidential form of government. During these changes, the patterns of recruitment into the higher public service in Nigeria have been influenced by both merit and non-merit criteria. Ethnic politics, educational imbalance among different states, and the need to ensure unity and stability were among several factors affecting recruitment patterns. The level and form of political role of the bureaucratic elite in Nigeria varied according to the type of regime in power, the quality of political leadership, and the prevailing constitutional arrangement.
Keywords: Bureaucracy -- Nigeria; Public administration -- Nigeria; Politics and government -- Nigeria